2008
DOI: 10.1016/j.jesp.2008.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Looking through the eyes of the powerful

Abstract: Across four experiments, we test the idea that power decreases metastereotyping, and that this effect is mediated by reduced perspective taking. Metastereotypes refer to the beliefs that members of group A share about the stereotypes that members of specific outgroup B typically have about ingroup A. We propose that the dominant psychological orientation of the powerless is aimed at seeing how others see them. In an intergroup situation they are therefore inclined to activate and apply metastereotypes. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 58 publications
2
70
1
1
Order By: Relevance
“…The fact that this manipulation required participants to put themselves into a high power position might be seen as limitation. However, the concept of power needs to be activated when the attraction of power is assessed and power research has demonstrated similar effects for the mere activation of the concept of power and the priming of a power role (e.g., Lammers, Gordijn, & Otten, 2008;Schmid Mast, Jonas, & Hall, 2009). Therefore, we believe that a priming of the construal of power as opportunity vs. responsibility that comes without the priming of a high power role, should demonstrate the same effect as the current studies.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that this manipulation required participants to put themselves into a high power position might be seen as limitation. However, the concept of power needs to be activated when the attraction of power is assessed and power research has demonstrated similar effects for the mere activation of the concept of power and the priming of a power role (e.g., Lammers, Gordijn, & Otten, 2008;Schmid Mast, Jonas, & Hall, 2009). Therefore, we believe that a priming of the construal of power as opportunity vs. responsibility that comes without the priming of a high power role, should demonstrate the same effect as the current studies.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Gordijn et al (2008) and are not specifically interested in the reactions of group members of low status groups. In our study, we chose a group that clearly occupies a low power and status position in society and this is important because these people are precisely the ones that meta-stereotype the most (Lammers et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this idea, Gordijn, Oldenhuis, and Otten (2008) found that only high prejudiced people expressed attitudes in line with an activated negative meta-stereotype. (Lammers, Gordijn, & Otten, 2008). Moroccan youth in the Netherlands occupies a relatively powerless position and Moroccan teenagers are therefore very likely to meta-stereotype.…”
mentioning
confidence: 99%
“…Future research could also investigate how seeking help from a judgemental outgroup is affected by the status hierarchy between the groups. If the outgroup's status is high, ingroup members may be particularly concerned about what that group thinks of their own group and such concerns may motivate stereotype disconfirming behavior (Lammers, Gordijn, & Otten, 2008). However, group members may also be concerned about revealing their needs before a high status outgroup (Nadler & Halabi, 2006), and how these potentially competing strategic concerns are balanced remains an empirical question.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%